2016
DOI: 10.1177/2380084416674670
|View full text |Cite
|
Sign up to set email alerts
|

Capnography Prevents Hypoxia during Sedation for Dental Treatment: A Randomized Controlled Trial

Abstract: Intravenous sedation is useful for dental treatment in patients with intellectual disabilities. However, it is often necessary to manage such patients with deep sedation because their cooperation cannot be obtained. During deep sedation, undetected hypoventilation can lead to severe complications, such as hypoxia. Recently, capnographic monitoring has been advocated as a useful technique for preventing hypoxia during sedation. This randomized control trial evaluated whether the use of capnography reduces the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…A lot of studies showed that capnography prevented 22 desaturation during sedation and the leading associations strongly recommend using it 43,44 . In our previous study, we had already shown its benefit in deep sedation for dental treatment 20 .…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…A lot of studies showed that capnography prevented 22 desaturation during sedation and the leading associations strongly recommend using it 43,44 . In our previous study, we had already shown its benefit in deep sedation for dental treatment 20 .…”
Section: Discussionmentioning
confidence: 94%
“…We employed an SpO2 of ≤94% to diagnose hypoxia. 20,42 Many recent studies have employed SpO2 values of <90% to indicate hypoxic episodes; hence, we evaluated milder hypoxic episodes than other studies. However, obese patients fall into desaturation more rapidly than non-obese patients; therefore, we consider that a milder hypoxic endpoint is logical for studying the sedation of obese patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence summary: The selection criteria for the literature search were prospective studies on capnography during sedation, with hypoxemia as an outcome. Twelve randomized studies with groups based on capnography use that compared the incidence of hypoxemia were selected [70][71][72][73][74][75][76][77][78][79][80][81]. Studies with fewer than 100 patients and those that included pediatric patients were excluded.…”
Section: Key Question 11 Does Capnography (End-tidal Carbon Dioxide M...mentioning
confidence: 99%